2022
DOI: 10.2147/ppa.s366966
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits of Safely Achieving Near Normoglycemia from the Perspective of People with Type 2 Diabetes: A Quantitative Survey Study

Abstract: Purpose To understand the perspectives of people with type 2 diabetes (T2D) on safely reaching near normoglycemia, defined as a glycated hemoglobin A1c (HbA1c) value of <6%. HbA1c indicates the average blood sugar level over the past few months. Patients and Methods This cross-sectional online quantitative survey of people with T2D asked about the current impacts of T2D, the anticipated benefits of safely achieving near normoglycemia among participants with a current Hb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…This result is not surprising given past research has demonstrated people with T2D in the US and UK place a great deal of importance on reaching near normoglycemia and associate this with a range of positive impacts. 18 , 19 Weight reduction also influenced preferences; however, this attribute was secondary to HbA1c reduction in both countries (US RAI: 18.3%; UK RAI: 17.3%). The RAI for delivery system was higher in the US (RAI: 20.9%) than in the UK (RAI: 9.2%), with patients in both countries preferring the single-use, pre-filled pen over the multi-use, dial-a-dose pen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result is not surprising given past research has demonstrated people with T2D in the US and UK place a great deal of importance on reaching near normoglycemia and associate this with a range of positive impacts. 18 , 19 Weight reduction also influenced preferences; however, this attribute was secondary to HbA1c reduction in both countries (US RAI: 18.3%; UK RAI: 17.3%). The RAI for delivery system was higher in the US (RAI: 20.9%) than in the UK (RAI: 9.2%), with patients in both countries preferring the single-use, pre-filled pen over the multi-use, dial-a-dose pen.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has demonstrated that improvements in HbA1c, and specifically reaching near normoglycemia, is both meaningful and important to people with T2D in the US and UK. 18,19 This study demonstrates that the properties of tirzepatide, a novel, weekly, GIP/GLP-1 RA for T2D are valuable to people with T2D living in the US and UK. The tirzepatide efficacy and safety profiles differ from those of other T2D treatments that are currently available.…”
mentioning
confidence: 81%
See 1 more Smart Citation